Tularemia in Bulgaria 2003-2004 - Radka Komitova; Rumiana Nenova; Plamen Padeshki; Ivan Ivanov; Vassil Popov; Petar Petrov (Journal of Infection in Developing Countries)
Introduction: Tularemia is an uncommon but potentially fatal zoonosis. А second outbreak of tularemia in Bulgaria, about 40 years after the first, occurred in 1997 in two western regions, near the Serbian border. In 2003 tularemia reemerged in the same foci. This retrospective study aimed to evaluate the clinical characteristics and the efficacy of antibiotic therapy in a tularemia resurgence in the Slivnitza region in 2003-2004.